THE RELATIONSHIP BETWEEN WORK-RELATED PSYCHOSOCIAL FACTORS AND WORK PERFORMANCE IN PRIVATE SECTOR COMPANY - Yi Wei, Lim (Universiti Malaysia Sarawak (UNIMAS), 2021)
Work-related psychosocial factors are the variables in the work environment that influence a healthy organization physically and mentally. Hence, a comfortable and healthy work environment should be built to support employee engagement and inspires their creativity and innovation in order to nurture a quality performance culture. There are many compositions include in the work-related psychosocial factors and four components were focused to be investigated in this study, such as role congruity, leadership styles, supervisory support, and organizational culture. This research aimed to study the relationship between work-related psychosocial factors and work performance in a private sector company. The influence of these four variables was studied among the employees in one of the private sectors in Penang, Malaysia. The target population of this study consists of 70 respondents in random departments with a sample size of 60 employees as respondents. A quantitative method was used in this study and the online questionnaires were distributed to the respondents to collect data. The data collected were analyzed by using Statistical Package for Social Science (SPSS) version 22.0. Pearson’s correlation analysis is used to test the impact of independent variables (role congruity, leadership styles, supervisory support, organizational culture) on employees’ work performance. The findings showed that all of the four psychosocial work factors had a significant relationship to employee work performance. Limitations and recommendations of the study were discussed further in this study.